2016
DOI: 10.1016/j.gdata.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variation in recently collected maize landraces from Mexico

Abstract: The present dataset comprises 36,931 SNPs genotyped in 46 maize landraces native to Mexico as well as the teosinte subspecies Zea maiz ssp. parviglumis and ssp. mexicana. These landraces were collected directly from farmers mostly between 2006 and 2010. We accompany these data with a short description of the variation within each landrace, as well as maps, principal component analyses and neighbor joining trees showing the distribution of the genetic diversity relative to landrace, geographical features and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 24 publications
5
69
0
3
Order By: Relevance
“…The use of Tripsacum instead of other members of the genus Zea was important to ensure no contemporary gene flow could produce artifacts in the inference of migration events and shared ancestral polymorphism. As no significant genetic structure was detected within maize landraces (15), we used all 161 individuals from 46 landraces as one population for all analyses. In the population graph, mexicana populations appear nested within parviglumis, with the Jalisco populations of parviglumis being ancestral (12Gua and 28Tol; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of Tripsacum instead of other members of the genus Zea was important to ensure no contemporary gene flow could produce artifacts in the inference of migration events and shared ancestral polymorphism. As no significant genetic structure was detected within maize landraces (15), we used all 161 individuals from 46 landraces as one population for all analyses. In the population graph, mexicana populations appear nested within parviglumis, with the Jalisco populations of parviglumis being ancestral (12Gua and 28Tol; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fig.1. individuals per landrace. Information about sampling, DNA extraction and genotyping can be found in (29).…”
Section: Some Authors Have Regarded Jalisco As An Important Center Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…These landraces are represented by 37 accessions from the Germplasm Bank of the International Maize and Wheat Improvement Center (CIMMYT) that were genotyped in this study (see below), plus 13 accessions from a previous study that used the same extraction protocol and SNP data generation (Arteaga et al, 2015). Our sample size for each landrace was 8–14 accessions, collected between 1946 and 2010 and covering most of the potential distribution of each landrace (see Supplementary Table 1 and Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Higher H e values for maize landraces from Mexico are expected because it is the center of origin of maize, and there is a wide range of environments that includes different altitudes and latitudes. Arteaga et al (2016) found that the distribution of genetic variation was better explained by environmental variables given by the interaction of altitude and latitude. Nevertheless, the diversity indices in our study were also comparable with the values reported by Rice et al (2006) for eight races from Mexico conserved ex situ, and with mean diversity indices reported by Sánchez-González (2011) for all races from Mexico.…”
Section: Genetic Diversity In the White Dent Collectionmentioning
confidence: 97%